Laparoscopic versus Open Appendicectomy: A Comparative Study - Ázaro, Euler M. (Society of Laparoendoscopic Surgeons, 1999)

(untitled)
There are many questions regarding the advantages and disadvatanges of a videolaparoscopic approach in the treatment of acute appendicits. The authors present the results of a non-randomized, prospective study with 496 patients admitted between January 1992 and March 1998 by the General Surgery Service of São Rafael Hospital -Salvador - BA - Brazil. The patients were submitted for appendicectomy by video laparoscopy or by the traditional open method, and variables such as surgery duration, morbidity, mortality, costs, and length of stay (LOS) were compared. The results demonstrate that laparoscopic appendicectomy is a safe alternative for treatment of acute appendicitis; however, there are several disadvantages that gradually must be overcome.